2011
DOI: 10.4103/0189-6725.79068
|View full text |Cite
|
Sign up to set email alerts
|

Complicated congenital splenic cyst: Saved by a splenunculus

Abstract: A 12-year-old girl presented with a large congenital splenic cyst complicated by Salmonella organisms. After failure of conservative management and percutaneous drainage, a splenectomy was performed. An incidental splenunculus was preserved. On follow up the splenunculus had increased to normal splenic size and there was no evidence of Howell-Jolly bodies, suggesting normal splenic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“… 1 On the other hand, females were found to be more affected by splenic cyst in general and congenital type in particular. 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“… 1 On the other hand, females were found to be more affected by splenic cyst in general and congenital type in particular. 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…The common organisms cultured from splenic abscess include Staphylococci, Streptococci, Salmonella and Escherichia coli although most of the microbiological data are from adult studies [9] . Salmonella has been isolated in 11–15% of splenic abscesses and has also been implicated as the causative organism in the immunocompetent child [2] , [3] , [10] . Salmonella is the most commonly identified cause of foodborne illness in U.S and most cases involve ingestion of contaminated food item [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Total splenectomy puts patients at risk of rare but life threatening overwhelming post-splenectomy sepsis. Percutaneous drainage is mostly a temporizing measure before interval surgery and is often complicated by recurrence of collections or incompletely emptied cavities, although some authors have reported good outcomes [1] , [2] , [3] , [16] . Choudhury et al reported a case series of 18 patients with isolated SA who were successfully managed with antibiotics and image-guided percutaneous drainage with all patients having complete resolution [16] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NPSC are classified based on the presence (congenital) or absence (post-traumatic) of epithelial lining [3]. Management of a non-parasitic splenic cyst is controversial: cystectomy, fenestration, percutaneous drainage and sclerotherapy, partial or total splenectomies have all been described [5], [6], [7], [8]; some authors conclude that splenic tissue preservation is recommended to avoid the overwhelming post-splenectomy infection (OPSI) [9]. Here in, we present our management of a splenic congenital cyst in a pediatric patient.…”
Section: Introductionmentioning
confidence: 99%